ChemInform Abstract: First‐Principles Molecular Dynamics Investigation on Na3AlF6 Molten Salt. Issue 27 (16th June 2016) - Lv, Xiaojun; Xu, Zhenming; Li, Jie; Chen, Jiangan; Liu, Qingsheng
Abstract: The partial radial distribution function, coordination numbers, bond angles, F atoms type, self‐diffusion coefficient, viscosity, and ionic conduction of molten Na3 AlF6 are investigated by first‐principles molecular dynamics simulation.